Comparative analysis of methods for assessing the safety of Dunaliella salina Teodoresco and Chlorococcum dissectum Korshikov (Chlorophyta) microalgae cultures after exposure to stress factors - Chernobai, N.A.; Vozovik, K.D.; Kadnikova, N.G. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2021)
The possibility of using various methods for determining the viability of cultures of microalgae Dunaliella salina and Chlorococcum dissectum before and after freezing-warming was investigated and analyzed. It has been established that the selection of an effective method should be carried out individually for each culture. For an integral assessment of the proliferative and metabolic activity of cells of both species of the studied microalgae, Alamar Blue-test and the ability to grow on liquid nutrient media can be used. The use of the Koch plate method, MTT-test and TTC staining is possible only for the microalga C. dissectum. Vital staining with trypan blue was found to be incorrect.